2013
DOI: 10.1007/s11302-013-9380-5
|View full text |Cite
|
Sign up to set email alerts
|

P2X1 receptor-mediated inhibition of the proliferation of human coronary smooth muscle cells involving the transcription factor NR4A1

Abstract: Adenine nucleotides acting at P2X 1 receptors are potent vasoconstrictors. Recently, we demonstrated that activation of adenosine A 2B receptors on human coronary smooth muscle cells inhibits cell proliferation by the induction of the nuclear receptor subfamily 4, group A, member 1 (NR4A1; alternative notation Nur77). In the present study, we searched for long-term effects mediated by P2X 1 receptors by analyzing receptor-mediated changes in cell proliferation and in the expression of NR4A1. Cultured human cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…Consistent with studies in smooth muscle cells [53] [54] , we found that NR4A1 reduces proliferation. However, in other studies, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with studies in smooth muscle cells [53] [54] , we found that NR4A1 reduces proliferation. However, in other studies, e.g.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it appears that T-type channels are more characteristic of the coronary myocytes from small animal models than of larger animals and humans. Third, while a number of voltage-independent Ca 2+ channels are expressed in coronary vascular smooth muscle, their roles are not entirely clear and may have more to do with, for example, cell proliferation than coronary vascular reactivity (476). In contrast, when it comes to regulating coronary vascular tone, L-type Ca 2+ channels clearly have the most dominant role, as: (i) diltiazem [a benzothiazepine-type Ca 2+ channel antagonist) blocks ~90% of myogenic tone in human coronary arterioles (674); (ii) nifedipine (a dihydropyrdine-type Ca 2+ channel antagonist) blocks 100% of agonist-induced tone in porcine coronary arterioles (50); and (iii) diltiazem completely eliminates coronary autoregulation, a mechanism that requires active coronary vasoconstriction (94) Figure 31].…”
Section: Ion Channels As End Effectorsmentioning
confidence: 99%
“…The vast majority of VSMC-preferentially expressed or -specific transcripts identified in our study were related to muscle differentiation and contractility. Apart from well-known VSMCs transcripts (such as Acta2, Myh11, desmin and Tgln ), our analysis highlighted the expression of markers like NR4a1 (coding for nuclear receptor subfamily 4, group A, member 1, involved in SMC proliferation) (Hinze et al, 2013; Yu et al, 2015), Pdlim3 (coding for actinin-associated LIM protein, involved in myocyte stability (Zheng et al, 2010), Mustn1 (regulating myoblast differentiation) (Hadjiargyrou, 2018; Liu et al, 2010), and Pln (coding for phospholamban, which regulates the sarcoplasmic reticulum Ca 2+ ATPase (SERCA) activity and muscle contractility) (Kranias and Hajjar, 2012). Surprisingly, about half of the genes were strongly upregulated on P15; this indicates that VSMC contractility continued to differentiate between P5 and P15.…”
Section: Discussionmentioning
confidence: 82%